Impacts of tree species admixing on soil carbon and soil properties in boreal conifer-dominated forests: Evidence from multiple datasets - Anna Repo; Päivi Soronen; Timo Domisch; Saija Huuskonen; Hannu Ilvesniemi; Aleksi Lehtonen; Jari Miina; Mari Myllymäki; Aino Smolander (Forest Ecology and Management, 2026)

Mixed forests can mitigate adverse effects of major disturbances on trophic interactions: Spruce dieback affecting wood ant foraging behaviour - Izabela Sondej; Timo Domisch (Forest Ecology and Management, 2025)

Waterlogging may reduce chemical soil C stabilization in forested peatlands - Jouni Kilpeläinen; Krista Peltoniemi; Paavo Ojanen; Päivi Mäkiranta; Sylwia Adamczyk; Timo Domisch; Raija Laiho; Bartosz Adamczyk (Soil Biology and Biochemistry, 2023)

The global EPTO database: Worldwide occurrences of aquatic insects - Afroditi Grigoropoulou; Suhaila Ab Hamid; Raúl Acosta; Emmanuel Olusegun Akindele; Salman A. Al‐Shami; Florian Altermatt; Giuseppe Amatulli; David G. Angeler; Francis O. Arimoro; Jukka Aroviita; Anna Astorga‐Roine; Rafael Costa Bastos; et al. (Global Ecology and Biogeography, 2023)
Motivation Aquatic insects comprise 64% of freshwater animal diversity and are widely used as bioindicators to assess water quality impairment and freshwater ecosystem health, as well as to test ecological hypotheses. Despite their importance, a comprehensive, global database of aquatic insect occurrences for mapping freshwater biodiversity in macroecological studies and applied freshwater research is missing. We aim to fill this gap and present the Global EPTO Database , which includes worldwide geo‐referenced aquatic insect occurrence records for four major taxa groups: Ephemeroptera, Plecoptera, Trichoptera and Odonata (EPTO). Main type of variables contained A total of 8,368,467 occurrence records globally, of which 8,319,689 (99%) are publicly available. The records are attributed to the corresponding drainage basin and sub‐catchment based on the Hydrography90m dataset and are accompanied by the elevation value, the freshwater ecoregion and the protection status of their location. Spatial location and grain The database covers the global extent, with 86% of the observation records having coordinates with at least four decimal digits (11.1 m precision at the equator) in the World Geodetic System 1984 (WGS84) coordinate reference system. Time period and grain Sampling years span from 1951 to 2021. Ninety‐nine percent of the records have information on the year of the observation, 95% on the year and month, while 94% have a complete date. In the case of seven sub‐datasets, exact dates can be retrieved upon communication with the data contributors. Major taxa and level of measurement Ephemeroptera, Plecoptera, Trichoptera and Odonata, standardized at the genus taxonomic level. We provide species names for 7,727,980 (93%) records without further taxonomic verification. Software format The entire tab‐separated value (.csv) database can be downloaded and visualized at https://glowabio.org/project/epto_database/ . Fifty individual datasets are also available at https://fred.igb‐berlin.de , while six datasets have restricted access. For the latter, we share metadata and the contact details of the authors.

Soil frost affects stem diameter growth of Norway spruce with delay - Tapani Repo; Timo Domisch; Jouni Kilpeläinen; Harri Mäkinen (Trees, 2021)
Key message A lack of snow cover and increased soil freezing may not only have short-term impacts on trees but longer-lasting lagged effects on radial growth. Abstract Soil temperature and soil frost intensity are affected by the depth of insulating snow cover and the timing of snowmelt which are predicted to change by climate warming. This may increase tree growth if there is less soil freezing or decrease growth if there is no insulating snow cover, but frost temperatures still exist. Previously, we showed that the changes in soil frost by snow manipulations in a ~ 50-year-old stand of Norway spruce [ Picea abies (L.) Karst.] in eastern Finland in two winters (2005/2006 and 2006/2007) led to short-term changes in physiology, morphology, and the growth of the shoots and roots. The treatments were: (1) control with natural insulating snow accumulation and melting; (2) snow removal during winter; and (3) snow removal in winter and insulation at the top of the forest floor in late winter to delay soil thawing. In this study, we examined the lagged effects of those treatments by radial trunk increment cores during the nine-year recovery period after the termination of the treatments. Annual ring width index (AWI) was calculated for each year by normalization of the ring width in the respective year in proportion to the ring width in the last year (2005) before the treatments. No differences in AWI were found between the treatments before or during the snow manipulation period. However, differences started to appear 1 year after the treatments were finished, became significant 4 years later in 2011 and lasted for 3 years. The radial increment was lower in the treatment with snow removed than in the control and in the treatment with insulation to delay soil thawing, but there were no differences between the latter two treatments. The results indicate that a lack of snow cover may not only have short-term impacts but longer-lasting consequences on the radial growth of trees. The positive effects of prolonged growing season by the increasing summer temperatures on forest growth predicted for the boreal region may therefore not be fully realised due to the negative effects of decreased snow cover and increasing soil freezing.

Ecotrons: Powerful and versatile ecosystem analysers for ecology, agronomy and environmental science - Jacques Roy; François Rineau; Hans J. De Boeck; Ivan Nijs; Thomas Pütz; Samuel Abiven; John A. Arnone; Craig V. M. Barton; Natalie Beenaerts; Nicolas Brüggemann; Matteo Dainese; Timo Domisch; et al. (Global Change Biology, 2021)
Ecosystems integrity and services are threatened by anthropogenic global changes. Mitigating and adapting to these changes require knowledge of ecosystem functioning in the expected novel environments, informed in large part through experimentation and modelling. This paper describes 13 advanced controlled environment facilities for experimental ecosystem studies, herein termed ecotrons, open to the international community. Ecotrons enable simulation of a wide range of natural environmental conditions in replicated and independent experimental units while measuring various ecosystem processes. This capacity to realistically control ecosystem environments is used to emulate a variety of climatic scenarios and soil conditions, in natural sunlight or through broad‐spectrum lighting. The use of large ecosystem samples, intact or reconstructed, minimizes border effects and increases biological and physical complexity. Measurements of concentrations of greenhouse trace gases as well as their net exchange between the ecosystem and the atmosphere are performed in most ecotrons, often quasi continuously. The flow of matter is often tracked with the use of stable isotope tracers of carbon and other elements. Equipment is available for measurements of soil water status as well as root and canopy growth. The experiments ran so far emphasize the diversity of the hosted research. Half of them concern global changes, often with a manipulation of more than one driver. About a quarter deal with the impact of biodiversity loss on ecosystem functioning and one quarter with ecosystem or plant physiology. We discuss how the methodology for environmental simulation and process measurements, especially in soil, can be improved and stress the need to establish stronger links with modelling in future projects. These developments will enable further improvements in mechanistic understanding and predictive capacity of ecotron research which will play, in complementarity with field experimentation and monitoring, a crucial role in exploring the ecosystem consequences of environmental changes.

Continental mapping of forest ecosystem functions reveals a high but unrealised potential for forest multifunctionality - Fons van der Plas; Sophia Ratcliffe; Paloma Ruiz‐Benito; Michael Scherer‐Lorenzen; Kris Verheyen; Christian Wirth; Miguel A. Zavala; Evy Ampoorter; Lander Baeten; Luc Barbaro; Cristina C. Bastias; Jürgen Bauhus; et al. (Ecology Letters, 2018)
Humans require multiple services from ecosystems, but it is largely unknown whether trade‐offs between ecosystem functions prevent the realisation of high ecosystem multifunctionality across spatial scales. Here, we combined a comprehensive dataset (28 ecosystem functions measured on 209 forest plots) with a forest inventory dataset (105,316 plots) to extrapolate and map relationships between various ecosystem multifunctionality measures across Europe. These multifunctionality measures reflected different management objectives, related to timber production, climate regulation and biodiversity conservation/recreation. We found that trade‐offs among them were rare across Europe, at both local and continental scales. This suggests a high potential for ‘win‐win’ forest management strategies, where overall multifunctionality is maximised. However, across sites, multifunctionality was on average 45.8‐49.8% below maximum levels and not necessarily highest in protected areas. Therefore, using one of the most comprehensive assessments so far, our study suggests a high but largely unrealised potential for management to promote multifunctional forests.

Biodiversity and ecosystem functioning relations in European forests depend on environmental context - Sophia Ratcliffe; Christian Wirth; Tommaso Jucker; Fons van der Plas; Michael Scherer‐Lorenzen; Kris Verheyen; Eric Allan; Raquel Benavides; Helge Bruelheide; Bettina Ohse; Alain Paquette; Evy Ampoorter; et al. (Ecology Letters, 2017)
The importance of biodiversity in supporting ecosystem functioning is generally well accepted. However, most evidence comes from small‐scale studies, and scaling‐up patterns of biodiversity–ecosystem functioning (B‐EF) remains challenging, in part because the importance of environmental factors in shaping B‐EF relations is poorly understood. Using a forest research platform in which 26 ecosystem functions were measured along gradients of tree species richness in six regions across Europe, we investigated the extent and the potential drivers of context dependency of B‐EF relations. Despite considerable variation in species richness effects across the continent, we found a tendency for stronger B‐EF relations in drier climates as well as in areas with longer growing seasons and more functionally diverse tree species. The importance of water availability in driving context dependency suggests that as water limitation increases under climate change, biodiversity may become even more important to support high levels of functioning in European forests.

Is Tree Species Diversity or Species Identity the More Important Driver of Soil Carbon Stocks, C/N Ratio, and pH? - Seid Muhie Dawud; Karsten Raulund-Rasmussen; Timo Domisch; Leena Finér; Bogdan Jaroszewicz; Lars Vesterdal (Ecosystems, 2016)

Does species richness affect fine root biomass and production in young forest plantations? - Timo Domisch; Leena Finér; Seid Muhie Dawud; Lars Vesterdal; Karsten Raulund-Rasmussen (Oecologia, 2015)

Respiration of wood ant nest material affected by material and forest stand characteristics - Veronika Jilkova; Timo Domisch; Zuzana Horicka; Jan Frouz (Biologia, 2013)

The Role of Wood Ants (Formica rufa group) in Carbon and Nutrient Dynamics of a Boreal Norway Spruce Forest Ecosystem - Leena Finér; Martin F. Jurgensen; Timo Domisch; Jouni Kilpeläinen; Seppo Neuvonen; Pekka Punttila; Anita C. Risch; Mizue Ohashi; Pekka Niemelä (Ecosystems, 2013)

Growth, carbohydrate and nutrient allocation of Scots pine seedlings after exposure to simulated low soil temperature in spring - Timo Domisch; Leena Finér; Tarja Lehto (Plant and Soil, 2002)

Corrigendum: Effect of soil temperature on nutrient allocation and mycorrhizas in Scots pine seedlings - Timo Domisch; Leena Finér; Tarja Lehto; Aino Smolander (Plant and Soil, 2002)

Effect of soil temperature on nutrient allocation and mycorrhizas in Scots pine seedlings - Timo Domisch; Leena Finér; Tarja Lehto; Aino Smolander (Plant and Soil, 2002)